The Need for Deployment Norms in Value Sensitive Data-Sharing Infrastructures - van de Wal, Christel; Dirksen, Vanessa; Bons, Roger; Versendaal, Johan (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Governmental deployment of decentralized data-sharing infrastructures embeds governance functions within technical architectures. Although Value Sensitive Design (VSD) is widely used to integrate public values into socio-technical design, practical uncertainty remains regarding its capacity to guide binding ex ante deployment decisions under conditions of value pluralism and institutional accountability. A normative conceptual analysis, informed by a conceptual literature review, identifies three justificatory limits of VSD in governmental deployment contexts: (i) the absence of ethical commitment, (ii) the reliance on empirical convergence without normative authority, and (iii) the lack of a mechanism for resolving value conflicts. These limits risk embedding value priorities as durable governance patterns. Governance-level justificatory standards are therefore required for accountable infrastructural deployment. To accommodate this, the paper concludes that an additional normative framework is required to guide accountable decision-making.